2016
DOI: 10.1177/0269881116678781
|View full text |Cite
|
Sign up to set email alerts
|

The Challenging Experience Questionnaire: Characterization of challenging experiences with psilocybin mushrooms

Abstract: Acute adverse psychological reactions to classic hallucinogens (“bad trips”, or “challenging experiences”), while usually benign with proper screening, preparation, and support in controlled settings, remain a safety concern in uncontrolled settings (such as illicit use contexts). Anecdotal and case reports suggest potential adverse acute symptoms including affective (panic, depressed mood), cognitive (confusion, feelings of losing sanity), and somatic (nausea, heart palpitation) symptoms. Responses to items f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
195
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 230 publications
(234 citation statements)
references
References 69 publications
(170 reference statements)
9
195
1
Order By: Relevance
“…Responses from a total of 1993 participants who provided useable data for an online survey of challenging experiences with psilocybin (Barrett et al, 2016; Carbonaro et al, 2016) were included in the current analyses. Analysis of Study 1 data constitutes a secondary analysis of previously reported data (Barrett et al, 2016; Carbonaro et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Responses from a total of 1993 participants who provided useable data for an online survey of challenging experiences with psilocybin (Barrett et al, 2016; Carbonaro et al, 2016) were included in the current analyses. Analysis of Study 1 data constitutes a secondary analysis of previously reported data (Barrett et al, 2016; Carbonaro et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of Study 1 data constitutes a secondary analysis of previously reported data (Barrett et al, 2016; Carbonaro et al, 2016). Participants were recruited to report on their single most psychologically difficult or challenging session or experience (worst “bad trip”) via internet advertisements (70.4% of respondents indicated that they became aware of the study through websites that are frequented by individuals interested in psychedelics such as Erowid, an online information library on psychoactive substances, www.erowid.com), email invitation via emails that were sent by study staff to email distribution lists related to websites and groups that are frequented by individuals interested in psychedelics (6.6% of respondents indicated that they received an email for the survey as a member of a large email distribution list, and 5.0% of respondents indicated that they received a personal email regarding the survey from a friend), and word of mouth (6.7% of respondents indicated that they became aware of the survey via personal communication other than email, and 0.9% of respondents indicated that they heard about the survey at a conference or public presentation).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations